2013
DOI: 10.1159/000350583
|View full text |Cite
|
Sign up to set email alerts
|

Higher Doses of Erythropoietin-Stimulating Agents and Hyporesponsiveness to Their Effects Are Associated with Increased Mortality among Prevalent Hemodialysis Patients

Abstract: Background: Attempts to achieve near-normal hemoglobin levels have been associated with higher mortality among chronic kidney disease patients. Evidence suggests a higher mortality rate for those with resistance to erythropoietin-stimulating agents (ESA). We investigated the association between responsiveness to ESA, dose of ESA and mortality in our hemodialysis population. Methods: A retrospective cohort study of chronic hemodialysis patients receiving dialysis was conducted at the University of Virginia faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 60 publications
(37 reference statements)
2
17
0
Order By: Relevance
“…However, about 5-10% of patients exhibit suboptimal responses to ESAs, despite receiving a high dose [1] and are dubbed to be hyporesponsive to ESAs. Given that ESA hyporesponsiveness subsequently leads to exacerbation of morbidity and mortality [2,3], this issue must be dealt with promptly. Several risk factors for ESA hyporesponsiveness have been identified [4], including inadequate iron administration [5], malnutrition [6,7], malignancy, vitamin deficiency [8] and administration of certain drug types, such as renin-angiotensin system inhibitors [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, about 5-10% of patients exhibit suboptimal responses to ESAs, despite receiving a high dose [1] and are dubbed to be hyporesponsive to ESAs. Given that ESA hyporesponsiveness subsequently leads to exacerbation of morbidity and mortality [2,3], this issue must be dealt with promptly. Several risk factors for ESA hyporesponsiveness have been identified [4], including inadequate iron administration [5], malnutrition [6,7], malignancy, vitamin deficiency [8] and administration of certain drug types, such as renin-angiotensin system inhibitors [9].…”
Section: Introductionmentioning
confidence: 99%
“…Fukuma et al [24] recently reported finding an association between ESA hyporesponsiveness and mortality in a large cohort of Japanese HD patients. More recently, Nishio et al [25] have shown associations of both higher degree of ESA resistance and higher doses of ESA with increased mortality among prevalent HD patients.…”
Section: Discussionmentioning
confidence: 99%
“…The followup period was adequate for analyzing the effects of the treatment on anemia parameters, but it was not valid for evaluating the long-term outcomes associated with each formulation. Further to above specified potential iron accumulation in tissues such as liver, heart and kidney, high doses of ESAs [43,44] and/or IV iron [45,46] have been linked to increased mortality in HD patients. In this study the use of iron sucrose similar is associated with higher ESA doses and higher IV iron doses, than with the IV iron original formulation.…”
Section: Discussionmentioning
confidence: 99%